Da’wah tourism: Formulation of collaborative governance perspective development - Susanto, Dedy; Musyafak, Najahan; Raharjo, Raharjo; Anasom, Anasom; Niswah, Uswatun; Hakim, Lukmanul (Jurnal Ilmu Dakwah, 2023)
Purpose - Departing from the phenomenon that the number of da’wah tourist destinations is quite large, especially the tombs of ulama', and the number of tourist visits have increased significantly, this study aims to describe the formulation of tourism destination development, describe collaborative governance in tourism destination development and describe the inhibiting and supporting factors of tourism destination development in Semarang City.Method - The type and approach of research used is descriptive with a qualitative approach. Data validity checks using data source triangulation techniques are carried out by comparing the results of observation data with interview data and interview results with related documents and data analysis through data reduction, data presentation, and conclusion drawing.Result - The results showed that the development of da’wah tourist destinations had yet to be carried out. However, there is a growth in the number of da’wah tourist destinations. Collaborative governance in the development of tourism destinations has yet to run optimally. There are several supporting and inhibiting factors in the development of tourism destinations.Implication - The formulation of the development of da'wah tourism in Semarang with collaborative covernance affects the maximum achievement of the professionalism of da'wah tourism services, completeness of facilities and infrastructure, reputation and credibility of the existing destination image so that tourists can feel safe and satisfied and increase their religious awareness. The results of this study are used to provide input to the Semarang city government, the Tourism Office, other related agencies to improve in connection with the development that has been done.Originality - This research is the first research related to da'wah tourism in Semarang City, where in this tourism development research uses a collaborative governance approach.***Tujuan - Berangkat dari adanya fenomena yang berupa jumlah destinasi wisata dakwah cukup banyak, terutama makam ulama’, dan jumlah kunjungan wisatawan mengalami kenaikan yang signifikan, maka penelitian ini bertujuan mendiskripsikan formulasi pengembangan destinasi pariwisata, mendeskripsikan collaborative governance dalam pengembangan destinasi pariwisata dan mendeskripsikan faktor penghambat dan pendukung pengembangan destinasi pariwisata di Kota Semarang.Metode - Tipe dan pendekatan penelitian yang digunakan adalah deskriptif dengan pendekatan kualitatif. Pemeriksaan keabsahan data dengan menggunakan teknik triangulasi sumber data yang dilakukan dengan membandingkan hasil data pengamatan dengan data hasil wawancara dan hasil wawancara dengan dokumen yang terkait, dan analisis data melalui reduksi data, penyajian data dan penarikan kesimpulan.Hasil  -  Hasil Penelitian menunjukkan bahwa, pengembangan destinasi wisata dakwah belum dilakukan secara keseluruhan akan tetapi terdapat pertumbuhan jumlah destinasi wisata dakwah, Collaboratie governance dalam pengembangan destinasi pariwisata belum berjalan maksimal dan terdapat beberapa faktor pendukung dan penghambat dalam pengembangan destinasi pariwisata.Implikasi – Formulasi pengembangan wisata dakwah di Semarang dengan collaborative covernance berpengaruh terhadap pencapaian yang maksimal terhadap profesionalitas pelayanan wisata dakwah, kelengkapan sarana dan prasarana, reputasi dan krebilitas citra destinasi yang ada sehingga wisatawan bisa merasa aman dan puas serta meningkatkan kesadaran beragama mereka. Hasil penelitian ini digunakan untuk memberikan masukan kepada pemerintah kota Semarang, Dinas Pariwisata, Dinas terkait lainnya untuk membenahi sehubungan dengan pengembangan yang telah dilakukan.Orisionalitas – Penelitian ini merupakan penelitian pertama terkait dengan wisata dakwah di Kota Semarang, di mana dalam penelitian pengembangan wisata ini menggunakan pendekatan collaborative governance.